Neurodevelopmental domain characteristics and their association with core symptoms in preschoolers with autism spectrum disorder in China: a nationwide multicenter study - Qian Zhang; Qiu Li; Ting Yang; Li Chen; Ying Dai; Hua Wei; Ke Wang; Feiyong Jia; Lijie Wu; Yan Hao; Ling Li; Jie Zhang; et al. (BMC Psychiatry, 2022)
Abstract Background Autism spectrum disorder (ASD) is a group of clinically heterogenic neurodevelopmental disorders, with intellectual disability being one of its common comorbidities. No large-sample, multicenter study has focused on the neurodevelopmental aspect of preschoolers with ASD. This study investigated the neurodevelopmental characteristics of preschoolers with ASD in China and explored the association between them and the core symptoms. Methods We enrolled 1019 ASD preschoolers aged 2–7 years old from 13 cities around China between May 2018 and December 2019, and used the revised Children Neuropsychological and Behavior Scale (CNBS-R2016) to assess their neurodevelopment. Their autistic core behaviors were evaluated based on their Social Responsiveness Scale (SRS), Autism Behavior Checklist (ABC), Child Autism Rating Scale (CARS), and communication warning behavior (CWB) scores in the CNBS-R2016. Results Based on general developmental quotient (GQ) < 70, 68.4% of the preschoolers with ASD had a developmental delay (DD), rated mild in 32.7% of them. The highest DD rate (> 70%) was found in language and personal-social skills, followed by fine motor skills (68.9%). Gross motor skills had the lowest DD rate (34.0%). We found that fine motor, language, and personal-social developmental quotients (DQs) were significantly lower than gross motor skills in no DD (GQ > 70), mild DD (GQ 55–69), and moderate and below DD groups (GQ ≤ 54). Furthermore, the DQs for language and personal-social skills were significantly lower than for gross and fine motor skills in both DD groups. The ABC, SRS, CARS, and CWB scores in the no DD group were the lowest, moderate in the mild DD group, and highest in the moderate and below DD group. Besides, negative correlations were found between the DQs of the four domains and the ABC, SRS, CARS, and CWB scores, of which the language and personal-social skills DQs had the strongest correlations. Conclusions Preschoolers with ASD had unbalanced neurodevelopment domain patterns and their neurodevelopmental levels were negatively correlated with the autism core symptoms. Hence, pediatricians should actively evaluate the neurodevelopment of children with ASD and conduct long-term follow-up during their early childhood to promote early diagnosis and develop personalized intervention plans. Trial registration ChiCTR2000031194 , registered on 03/23/2020.